ELASTIC PROPERTIES OF ROCKS - Karagianni, A.; Karoutzos, G.; Ktena, S.; Vagenas, N.; Vlachopoulos, I.; Sabatakakis, N.; Koukis, G. (Bulletin of the Geological Society of Greece, 2010)
The aim of this paper is to determine the elastic parameters of some rocks and especially limestones, schist, sandstones, conglomerates, peridotites and granites using a large number of laboratory tests performed on intact rock samples. The range of values for Young`s modulus and uniaxial compressive strength is evaluated, while the relationship between elastic and strength parameters is defined. Regression analyses were applied to define relations among these parameters and the range of values of modulus ratio (MR) is estimated for each rock type.